FORECASTING COVID-19 IN INDONESIA WITH VARIOUS TIME SERIES MODELS - Gumgum Darmawan; Dedi Rosadi; Budi Nurani Ruchjana; Resa Septiani Pontoh; Asrirawan Asrirawan; Wirawan Setialaksana (MEDIA STATISTIKA, 2022)
In this study, Covid-19 modeling in Indonesia is carried out using a time series model. The time series model used is the time series model for discrete data. These models consist of Feedforward Neural Network (FFNN), Error, Trend, and Seasonal (ETS), Singular Spectrum Analysis (SSA), Fuzzy Time Series (FTS), Generalized Autoregression Moving Average (GARMA), and Bayesian Time Series. Based on the results of forecast accuracy calculation using MAPE (Mean Absolute Percentage Error) as model evaluation for confirmed data, the most accurate case models is the bayesian model of 0.04%, while all recovered cases yield MAPE 0.05%, except for FTS = 0.06%. For data for death cases SSA and Bayesian Models, the best with MAPE is 0.07%.